The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1089/sur.2017.295
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Predictors of Early Infection after Heart Transplantation

Abstract: Prior mechanical circulatory support and the acute need for CRRT may predispose OHT patients to an infection early in the post-operative period. Evaluation of peri-operative antimicrobial prophylaxis, based on an individual center's resistance panels, may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…In this study, the major cause of 30-day mortality was an infection in patients with pre-transplant RRT. Previous studies have reported that pre-transplant RRT was a major risk factor of post-transplant BSI in HT ( 2 , 25 ). Both use of RRT and MCS before HT would further increase the risk of BSI before and after HT ( 12 , 26 ).…”
Section: Discussionmentioning
confidence: 98%
“…In this study, the major cause of 30-day mortality was an infection in patients with pre-transplant RRT. Previous studies have reported that pre-transplant RRT was a major risk factor of post-transplant BSI in HT ( 2 , 25 ). Both use of RRT and MCS before HT would further increase the risk of BSI before and after HT ( 12 , 26 ).…”
Section: Discussionmentioning
confidence: 98%
“…Bacterial infections have become the most frequent and challenging infections in SOT recipients [2,13,14]. Among bacterial infections, BSI are those associated with the highest mortality rates, which can reach 30% in heart transplant patients [15] and 25% in lung transplanted patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…Bloodstream infections (BSIs) represent a major complication of solid organ transplant (SOT) and are among the leading causes of morbidity and mortality in patients [1,2]. Overall, the rate of BSIs ranges from 8.6% to 26%, depending on transplantation type [3].…”
Section: Introductionmentioning
confidence: 99%
“…Multivariate analysis revealed that hypertension and pre‐operative eGFR were significant predictors of unplanned readmission, suggesting that pre‐operative hypertension and renal function are important variables for readmission. This indicates that cardiovascular and renal function affect factors leading to death or readmission in 1 year after heart transplantation (McAdams‐DeMarco et al, ; Shultes et al, ) and that medication‐induced complications due to immunosuppressant administration after transplantation influences readmission (Hunt & Haddad, ). Therefore, these findings could aid in the development of interventions for the prevention and reduction of unplanned readmission through intensive postoperative care management of patients with risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, disease-related factors include indication for heart transplantation (Doesch et al, 2010), pre-operative intensive care unit (ICU) and hospital admission (Ohe, 2012) and inotropic agent and medical device use (Weber et al, 2014). Lastly, therapeutic factors include haemodialysis (Shultes et al, 2018), cold ischaemic time (Ahn et al, 2017), pre-and postoperative laboratory data (Huang et al, 2008) and prescribed medication after the operation, such as immunosuppressants and cholesterol synthesis inhibitors (Kittleson & Kobashigawa, 2013;Kong, 2009).…”
Section: Introductionmentioning
confidence: 99%